Understanding the Interplay Between Family Roles and Psychological Well-Being in Supporting the Natural Development of the Childs - Melina, Eri; Shodiq, Sadam Fajar (FKIP Universitas Lampung, 2024)
Understanding the Interplay Between Family Roles and Psychological Well-Being in Supporting the Natural Development of the Childs. Objective: This study aims to investigate the impact of family dynamics and children’s psychological well-being on their overall development. Specifically, it explores how the family environment and psychological well-being influence the development of a child’s innate nature. Methods: A quantitative descriptive approach was employed in this study, utilizing a linear regression model. The sample was drawn from Islamic high schools (or equivalent) in Purworejo Regency, with respondents selected using a random sampling technique. Data were collected through questionnaires measuring family dynamics and the psychological well-being of children. Findings: The findings reveal that the family plays a crucial role in shaping the character development of children. Additionally, children’s psychological well-being has a significant impact on their overall development. The analysis shows that both family dynamics and psychological well-being interact to facilitate the optimal development of a child’s inherent characteristics. Conclusion: Based on the findings, it can be concluded that both psychological well-being and family roles significantly contribute to a child's development. Therefore, it is essential to consider both factors in efforts to support the best development of a child’s innate traits, ensuring they reach their full potential. Keywords: family roles, psychological well-being, natural development of the childs.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024137